miR-195 inhibits tumor progression by targeting RPS6KB1 in human prostate cancer - Cai, Chao (Clin Cancer Res, 2015)
PURPOSE: To investigate the involvement of hsa-microRNA-195-5p (miR-195) in progression and prognosis of human prostate cancer (PCa). EXPERIMENTAL DESIGN: qRT-PCR was performed to detect miR-195 expression in both PCa cell lines and clinical tissue samples. Its clinical significance was statistically analyzed. The roles of miR-195 and its candidate target gene ribosomal protein S6 kinase, 70kDa, polypeptide 1 (RPS6KB1) in PCa progression were confirmed based on both in vitro and in vivo systems. RESULTS: MiR-195 downregulation in PCa tissues was significantly associated with high Gleason score (P=0.001), positive metastasis failure (P<0.001) and biochemical recurrence (BCR, P<0.001). Survival analysis identified miR-195 as an independent prognostic factor for BCR-free survival of PCa patients (P=0.022). Then, we confirmed the tumor suppressive role of miR-195 through PCa cell invasion, migration and apoptosis assays in vitro, along with tumor xenografts growth, angiogenesis and invasion in vivo according to both gain-of-function and loss-of-function experiments. Additionally, RPS6KB1 was identified as a novel direct target of miR-195 through proteomic expression profiling combined with bioinformatic target prediction and luciferase reporter assay. Moreover, the re-expression and knockdown of RPS6KB1 could respectively rescue and imitate the effects induced by miR-195. Importantly, RPS6KB1 expression was closely correlated with aggressive progression and poor prognosis in PCa patients as opposed to miR-195. Furthermore, we identified MMP-9, VEGF, BAD and E-cadherin as the downstream effectors of miR-195-RPS6KB1 axis. CONCLUSION: The newly identified miR-195-RPS6KB1 axis partially illustrates the molecular mechanism of PCa progression and represents a novel potential therapeutic target for PCa treatment.